The correlation between endometrial thickness and outcome of in vitro fertilization and embryo transfer (IVF-ET) outcome - Al-Rejjal Rafat; Al-Hassan Saad; Coskun Serdar; Al-Ghamdi Ahlam; Awartani Khalid (BMC, 2008)
Abstract Background To evaluate the relationship between endometrial thickness on day of human chorionic gonadotrophin administration (hCG) and pregnancy outcome in a large number of consecutive in vitro fertilization and embryo transfer (IVF-ET) cycles. Methods A retrospective cohort study including all patients who had IVF-ET from January 2003-December 2005 conducted at a tertiary center. Results A total of 2464 cycles were analysed. Pregnancy rate (PR) was 35.8%. PR increased linearly (r = 0.864) from 29.4% among patients with a lining of less than or equal to 6 mm, to 44.4% among patients with a lining of greater than or equal to 17 mm. ROC showed that endometrial thickness is not a good predictor of PR, so a definite cut-off value could not be established (AUC = 0.55). Conclusion There is a positive linear relationship between the endometrial thickness measured on the day of hCG injection and PR, and is independent of other variables. Hence aiming for a thicker endometrium should be considered.